Pemanfaatan limbah kulit kakao menjadi briket arang sebagai bahan bakar alternatif dengan penambahan ampas buah merah - Syarifhidayahtullah Syarifhidayahtullah; Rochim Bakti Cahyono; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2019)
The conversion of cocoa shell waste into char briquettes has been carried out through various methods. However, the product characteristics do not meet the SNI briquettes requirements. Therefore, it is necessary to improve process engineering by mixing cocoa peel waste with red fruit pulp to get char briquettes in order to improve quality of briquette products. This research was carried out through pyrolysis process with temperthwatures up to 500 oC and held for 4 hours. The research objective was to produce char briquettes from cacao pod shell waste with the addition of red fruit pulp and its characteristic test. The study was designed with 2 variables, namely independent variables in the form of char raw material powder that passed 50 mesh sieve, weight ratio of cocoa shell char powder and red fruit pulp char powder (100:0, 70:30, 50:50, 30:70, and 0%:100%), pressure (100 kg/cm2), 10% starch adhesive from raw materials, and briquette diameter of 40 mm. Whereas the dependent variables are the moisture content (%), volatile content (%), ash content (%), fixed carbon content (%), and calorific value (cal/g). The results showed that the process of pyrolysis of char briquettes waste cocoa shell with red fruit pulp can increase its calorific value. The best characteristics of briquette were obtained from mixed briquettes (composition of 30%:70%) with moisture content of 5.63%, volatile content of 18.65%, ash content of 9.45%, fixed carbon content of 66.27%, and calorific value of 6422 cal/g.